Superior Ion‐Conducting Hybrid Solid Electrolyte for All‐Solid‐State Batteries. Issue 4 (13th November 2014) - Kim, Jae‐Kwang; Scheers, Johan; Park, Tae Joo; Kim, Youngsik
Abstract Herein, we developed a high‐performance lithium ion conducting hybrid solid electrolyte, consisted of LiTFSI salt, Py14TFSI ionic liquid, and TiO2 nanoparticles. The hybrid solid electrolyte prepared by a facile method had high room temperature ionic conductivity, excellent thermal stability and low interface resistance with good contact. In addition, the lithium transference number was highly increased by the scavenger effect of TiO2 nanoparticles. With the hybrid solid electrolyte, the pouch‐type solid‐state battery exhibited high initial discharge capacity of 150 mA h g−1 at room temperature, and even at 1 C, the reversible capacity was as high as 106 mA h g−1.